Chapter Bodies of Tow and Paraffin - Méndez Baiges, Maite (Studi e saggi, 2022)
"Bodies of tow and paraffin" is the phrase used by Georges Braque, pioneer with Picasso of Cubism, to describe the alarm that he felt at his first sight of Les Demoiselles d'Avignon when he paid Picasso a visit as he was painting it in the Bateau Lavoir in 1907. This sums up well the reactions the work produced among the friends of the Spanish painter who first saw it. This chapter summarises these first reactions of horror, disgust and disappointment felt among Picasso's friends and acquaintances. It also provides a host of comments and quotes made by Picasso himself, remarkable for their contradictions and high dosages of irony.